Anticancer potential of dietary vitamin D and ascorbic acid: A review. Issue 12 (13th August 2017) - Sunil Kumar, B. V.; Singh, Satparkash; Verma, Ramneek
ABSTRACT: Cancers have been the leading cause of death worldwide and poor diet and physical inactivity are major risk factors in cancer-related deaths. Micronutrients such as vitamins and minerals appear to have preventive properties against cancer. One important mechanism by which dietary changes can exert preventive effects on cancer is via the modulation of micronutrient concentrations in target tissues. Many of these micronutrients are available in the form of dietary supplements, and the intake of these supplements is prevalent in various parts of the world. However, in most cases, it is not known which micronutrient (or combination of micronutrients) is best when it comes to lowering the risk of cancer. The present review illustrates the effect of vitamin D and ascorbic acid intake on preventing cancer.